English Communication Problems and Needs from Social Engagement Perspective as Experienced by Airport Passenger-Handlers - Cahyani, Anisa Putri; Drajati, Nur Arifah (Universitas Islam Negeri Raden Intan Lampung, 2017)
Airport and airlines service demand qualified employees to have proficient English communication skill to support smooth flow of airport and flights operation, primarily the workers involved in passenger-handling. English for Specific Purpose (ESP) course which fulfills the target needs could help such situation. This small scale study presents stakeholders’ comments about the staffs’ English communication ability and needs in the work setting (data collected through semi-structured interview) and problem of English communication encountered by the currently working staffs (through open-ended questionnaires as preliminary data and extended group interview or discussion). This paper reflects the experience of the airport passenger-handlers in Indonesia regarding with their challenges in performing English oral communication in the workplace. Analyzed from the perspective of social engagement, the problems and needs found in this study are possible to be the basis for ESP material betterment in the related field.